1996
DOI: 10.1021/ma950920f
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Laboratory Slurry Reactor for Ethylene Polymerization Studies

Abstract: A novel laboratory slurry reactor useful for studies of polymerization of olefins with solid catalysts such as Cr/silica is described. The operation of this reactor, in which gaseous impurities are minimized by purification of incoming gases and by in situ activation of the catalyst, has enabled the early stages of the homopolymerization of ethylene to be studied without interference from catalyst deactivation effects. By standardizing the conditions for the experimental runs, the reactor demonstrated its usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Rebenstorf 319 obtained, at a temperature of 353 K and at an ethylene pressure of 500 Torr, a TOF of about 0.44 C 2 H 4 molecules/s. Szymura et al 320 reported a polymer yield of 25.5 g (PE)/g (catalyst) for a 300 m 2 /g silica loaded with 5 wt % Cr, during polymerization at 300 K and atmospheric pressure over a COprereduced catalyst. This value corresponds to a TOF of about 0.26 C 2 H 4 molecules/s at atmospheric pressure.…”
Section: Concentration Of Activementioning
confidence: 99%
See 1 more Smart Citation
“…Rebenstorf 319 obtained, at a temperature of 353 K and at an ethylene pressure of 500 Torr, a TOF of about 0.44 C 2 H 4 molecules/s. Szymura et al 320 reported a polymer yield of 25.5 g (PE)/g (catalyst) for a 300 m 2 /g silica loaded with 5 wt % Cr, during polymerization at 300 K and atmospheric pressure over a COprereduced catalyst. This value corresponds to a TOF of about 0.26 C 2 H 4 molecules/s at atmospheric pressure.…”
Section: Concentration Of Activementioning
confidence: 99%
“…Of course, it is very difficult to compare these three values, because they have been obtained in different conditions of temperature and pressure on catalysts characterized by different chromium concentrations and different activation procedures. Nevertheless, we can try to convert reported TOF values 133,319,320 into the expected TOF values for a polymerization reaction conducted in conditions typical of spectroscopic characterization experiments, i.e., RT and low ethylene pressure (20 Torr). As the spread in the temperature adopted in the three experiments is quite small (300-353 K), in this simple conversion, the temperature effects can be neglected.…”
Section: Concentration Of Activementioning
confidence: 99%
“…The polymerization experiments reported by Szymura et al 24 give us a feeling of how our model catalyst performs in comparison to the industrial chromium on silica. These authors tested a series of chromium on high surface area silica for ethylene polymerization in a slurry reactor at 25 "C. Although the catalyst pre-treatment was more involved than ours, the calcination step, 500 "C in O,, is close to the activation temperature we used for the model catalyst.…”
Section: Polyethylene Formationmentioning
confidence: 99%
“…1) support this observation. This fragmentation effect, which is particularly important when the rate of polymerization is high and when enough polymer to push the particles apart has been formed, has already been observed both in Cr/SiO 2 12 and in silica‐supported metallocene catalysts 8, 13…”
Section: Resultsmentioning
confidence: 72%